National Center for catastrophic sport injury research: Twentysixth annual report fall 1982 - spring 2008 - Müller, F. O.; Cantu, R. C.
In 1931 the American Football Coaches Association initiated the First Annual Survey of Football Fatalities and this research has been conducted at the University of North Carolina at Chapel Hill since 1965. In 1977 the National Collegiate Athletic Association initiated a National Survey of Catastrophic Football Injuries which is also conducted at the University of North Carolina. As a result of these research projects important contributions to the sport of football have been made. Most notable have been the 1976 rule changes, the football helmet standard, improved medical care for the participants and better coaching techniques. Due to the success of these two football projects the research was expanded to all sports for both men and women, and a National Center for Catastrophic Sports Injury Research was established. The decision to expand the research was based on the following factors: 1. Research based on reliable data is essential if progress is to be made in sports safety. 2. The paucity of information on injuries in all sports. 3. The rapid expansion and lack of injury information in women's sports. For the purpose of this research the term catastrophic is defined as any severe injury incurred during participation in a school/college sponsored sport. Catastrophic will be divided into the following three definitions: 1. Fatality 2. Non-Fatal - permanent severe functional disability. 3. Serious - no permanent functional disability but severe injury. An example would be a fractured cervical vertebra with no paralysis. Sports injuries are also considered direct or indirect. The definition for direct and indirect is as follows: Direct - Those injuries which resulted directly from participation in the skills of the sport. Indirect - Those injuries which were caused by systemic failure as a result of exertion while participating in a sport activity or by a complication which was secondary to a non-fatal injury.